Pseudo-Subarachnoid Hemorrhage; Chronic Subdural Hematoma with an Unruptured Aneurysm Mistaken for Subarachnoid Hemorrhage - Son, Dookyung (Korean J Neurotrauma, 2019)
Subarachnoid hemorrhage (SAH) usually occurs due to aneurysmal rupture of intracranial arteries and its typical computed tomography (CT) findings are increased attenuation of cisterns and subarachnoid spaces. However, several CT findings mimicking SAH are feasible in diverse conditions. They are so-called as pseudo-SAH, and this report is a case of pseudo-SAH which is misdiagnosed as aneurysm rupture accompanied by bilateral chronic subdural hematoma (cSDH). A 42-year-old male with severe headache visited our institute. Non-contrast brain CT images showed increased attenuation on basal cistern, and cSDH on both fronto-temporo-parietal convexity with midline shifting. Trans-femoral cerebral angiography was done and we confirmed small aneurysm at right M1 portion of middle cerebral artery. Under diagnosis of SAH, we planned an operation in order to clip aneurysmal neck and remove cSDH. cSDH was removed as planned, however, there was no SAH and we also couldn't find the rupture point of aneurysm. Serial follow-up CT showed mild cumulative cSDH recurrence, but the patient was tolerant and had no neurologic deficit during hospitalization. We have checked the patient via out-patient department for 6 months, there are no significant changes in volume and density of cSDH and the patient also have no neurologic complications.